Sustainable Biomass-to-Energy Transformation : Choline Chloride Based Deep Eutectic Solvent for Lignin Extraction and Liquefaction - Elatta, Odita; Yiin, Chung Loong; Jennie Ngu, Siew Zhen; Armando T., Quitain; Serene Lock, Sow Mun; Bridgid Chin, Lai Fui; Md Rezaur, Rahman (The Italian Association of Chemical Engineering, 2023)
Biomass is often renowned as one of the inexpensive and largest sources of non-depleting energy in the world, attributed to its great potential for continuous and sustainable supply of energy in the form of biofuels and various value-added products. With the increasing demand to preserve the environment, the use of green solvents, such as deep eutectic solvents (DESs), is desirable, given their capability to reduce the generation of hazardous substances. In this work, choline chloride based DESs have been used to extract lignin from biomass. The structure and thermal stability of the extracted lignin are analysed using Fourier-transform infrared spectroscopy (FT-IR) and thermogravimetric analysis (TGA), respectively. FT-IR spectra revealed that chemical properties of lignin were determined through absorbance peaks corresponding to hydroxyl and C-H stretching, as well as the presence of carbonyl moieties and phenolic groups. TGA analysis of lignin showed weight loss peaks at 66 °C, 256 °C, and 319 °C, with major weight loss at 200 - 350 °C due to lignin degradation and release of monomeric phenols, resulting in a final residue consisting of non-volatile solids associated with condensed aromatic structures and lignin ash at 740 °C. The extracted lignin was then subjected to subcritical water-supercritical CO2 hydrothermal liquefaction (HTL) and converted into bio-oil. In this context, HTL proves its benefits by providing the highest yield of 77.41 % using optimum parameters of lignin-to-water ratio (1:5), pressure (20 MPa), temperature (275 °C) and time (60 min). The functional groups of bio-oil derived from the extracted lignin were analysed using FT-IR, which proves the functional groups (phenols, carboxylic acid, ketones, carboxylic acid, esters and aromatic groups) present in the bio-oil. Detailed information regarding the HTL of lignin derived from biomass, which circumvents the need for energy-intensive drying procedures, is critical in mitigating the challenges posed by the abundance of biomass residues.